2022
DOI: 10.3389/fvets.2022.813800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coated Sodium Butyrate and Polysaccharides From Cordyceps cicadae on Intestinal Tissue Morphology and Ileal Microbiome of Squabs

Abstract: This experiment was conducted to investigate the effects of dietary supplementation with different levels of coated sodium butyrate (CSB) and polysaccharides extracted from Cordyceps cicadae (CCP) on growth performance, intestinal tissue morphology and ileum microbiome in squabs. A total of 420 1-day-old squabs were randomly divided into seven groups with 5 replicates each and 12 squabs per replicate. The squabs were fed basal diet (control group) and basal diet supplemented with different levels of CSB (275, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
(63 reference statements)
2
5
0
Order By: Relevance
“…Due to CSB supplementation, Bacteroidetes were not required for butyrate production to maintain the normal activity of the organism, which explains the significantly lower abundance of Bacteroidetes in the group CSB compared to the control group, which is consistent with the results of our previous studies ( 67 , 68 ). Furthermore, in our previous study, we found that CSB increased the abundance of Actinobacteria in the ileum of suckling pigeons ( 12 ), which is consistent with the results of this pilot study. Actinobacteria have great economic importance owing to their secondary metabolites, which have antibiotic properties ( 69 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Due to CSB supplementation, Bacteroidetes were not required for butyrate production to maintain the normal activity of the organism, which explains the significantly lower abundance of Bacteroidetes in the group CSB compared to the control group, which is consistent with the results of our previous studies ( 67 , 68 ). Furthermore, in our previous study, we found that CSB increased the abundance of Actinobacteria in the ileum of suckling pigeons ( 12 ), which is consistent with the results of this pilot study. Actinobacteria have great economic importance owing to their secondary metabolites, which have antibiotic properties ( 69 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, SB is less palatable as a feed additive due to its unpleasant odor and volatility. Coating SB in palm oil (coated sodium butyrate, CSB) improves its palatability, allowing its use as a feed additive ( 12 ). SB-supplementation is thought to improve the development ( 13 , 14 ) and morphological structure of the intestinal mucosa and regulate the growth of commensal intestinal flora.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolite of Firmicutes is mainly butyric acid, including members of the Ruminococcus and Spirulina, which can promote energy absorption in the gut (Chen and Xu, 2015;Komaroff, 2017;Louis and Flint, 2017), and metabolites of the genus Bacteroides can affect the absorption of nutrients by animals (Pittayanon et al, 2019;Robles-Vera et al, 2020). Butyric acid, a key substance for colon health and integrity, is the main metabolic substrate for coliforms, providing at least 60%-70% of their energy requirements for proliferation and differentiation (Sun et al, 2022). At the genus level, the abundances of Megamonas in the group LRFI were higher than in the HRFI and the abundances of Anaerobiospirillum in the group LRFI were lower than in the HRFI.…”
Section: Discussionmentioning
confidence: 99%
“…The butyrate applied in this study is coated, which was previously found to result in the slow release of butyrate along the length of the intestinal tract [50,51]. Sun et al, 2022, has shown that coated butyrate can reduce the abundance of enterococci in the ileum microbiota of squabs [52], but this is the first time this function is demonstrated in broilers. E. hirae is an opportunistic pathogen that can cause locomotion problems, endocarditis and septicaemia in broiler chickens [53][54][55][56].…”
Section: Discussionmentioning
confidence: 95%